Efficacy evaluation of antidepressant drugs utilized at tertiary care centre in North Karnataka in psychiatric outpatient department - Bagewadi, Harish G.; Huded, Chandrashekar B. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Depression is the major psychotic disorder affecting 9.5% of population worldwide. Present study investigates the prescribing patterns of different antidepressants evaluating their efficacy. Methods: This was a prospective, observational study which was conducted in the out-patient department of Psychiatry and Pharmacology in Gulbarga Institute of Medical Sciences, Kalaburagi. A total of 200 cases were enrolled for the present study. Statistical analysis for efficacy was done using Wilcoxson’s signed rank test. Results: Predominantly, females suffered from depression when compared to male counterparts. In our study, monotherapy was practiced more frequently than polytherapy with 2 or more drugs. Selective serotonin reuptake inhibitors (SSRIs) like Escitalopram was found out to be the most widely used antidepressant drug. Conclusions: Among antidepressant medications, SSRIs are preferred over others because of their better side effect profile.